2015
DOI: 10.1016/s2214-109x(14)70344-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an integrated intimate partner violence and HIV prevention intervention in Rakai, Uganda: analysis of an intervention in an existing cluster randomised cohort

Abstract: Summary Background Intimate partner violence (IPV) is associated with HIV infection. We aimed to assess whether provision of a combination of IPV prevention and HIV services would reduce IPV and HIV incidence in individuals enrolled in the Rakai Community Cohort Study (RCCS), Rakai, Uganda. Methods We used pre-existing clusters of communities randomised as part of a previous family planning trial in this cohort. Four intervention group clusters from the previous trial were provided standard of care HIV serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
330
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(340 citation statements)
references
References 40 publications
9
330
1
Order By: Relevance
“…36 Other clinical trials of IPV interventions, such as the SHARE trial, 37 have found similar results; that is, the ethical obligation of providing abused women with referral information provided at least some intervention. Furthermore, continued assessment for IPV during data collection may have heightened women's motivation to address their concerns.…”
Section: Discussionmentioning
confidence: 90%
“…36 Other clinical trials of IPV interventions, such as the SHARE trial, 37 have found similar results; that is, the ethical obligation of providing abused women with referral information provided at least some intervention. Furthermore, continued assessment for IPV during data collection may have heightened women's motivation to address their concerns.…”
Section: Discussionmentioning
confidence: 90%
“…Studies also focused on HIV testing and intervention to promote safe HIV disclosure, risk reduction and community mobilization to change norms, behaviours and attitudes for intimate partner violence [17]. Microfinance and training interventions along with gender and HIV training [18] and Cost effective orphan girl's school intervention program [19] was also found in our review.…”
Section: Types Of Interventionsmentioning
confidence: 93%
“…This review involved an extensive research but we focused on interventions that adopted high quality study designs such as RCTs [14][15][16][17][18][19] before and after cross-sectional [20,21], longitudinal [22] and pre-post-tests [23].…”
Section: Study Designsmentioning
confidence: 99%
“…According to a National family and health survey in 2005, total lifetime prevalence of domestic violence was 33.5% and 8.5% for sexual violence among women aged 15-49. A 2014 study in the Lancet reports that the reported sexual violence rate in India is among the lowest in the world, the large population of India means that the violence affects 27·5 million over women their lifetime (Wagman et al 2015).…”
Section: Introductionmentioning
confidence: 99%